1992
DOI: 10.1597/1545-1569_1992_029_0531_ccotnp_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Clefts of the Nose: Principles of Surgical Management

Abstract: Congenital clefts of the nose are rare and highly variable. Because there are few examples, standard methods for treatment do not exist. Therefore each patient must be evaluated and managed individually with respect to anatomic elements, timing, and sequence of reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The surgical management of rare craniofacial clefts is a challenge, given the small number of techniques published, the lack of standardized guidelines, and the variability in clinical presentation (Tessier, 1969a,b;Tessier et al, 1977;Van der Meulen, 1985;Van der Meulen and Vaandrager, 1989;Shewmake and Kawamoto, 1992;Mishira and Purwar, 2009;Laure et al, 2010;da Silva Freitas et al, 2010;Bütow and Botha, 2010;Hou et al, 2011). We report a very severe Tessier 3 cleft with bilateral microphthalmia.…”
Section: Discussionmentioning
confidence: 83%
“…The surgical management of rare craniofacial clefts is a challenge, given the small number of techniques published, the lack of standardized guidelines, and the variability in clinical presentation (Tessier, 1969a,b;Tessier et al, 1977;Van der Meulen, 1985;Van der Meulen and Vaandrager, 1989;Shewmake and Kawamoto, 1992;Mishira and Purwar, 2009;Laure et al, 2010;da Silva Freitas et al, 2010;Bütow and Botha, 2010;Hou et al, 2011). We report a very severe Tessier 3 cleft with bilateral microphthalmia.…”
Section: Discussionmentioning
confidence: 83%
“…When managed successfully such patients become beautiful feathers in the cap of our surgical careers. Initial attempts to describe the rare facial clefts were done by Davis [4], Blackfield and Wilde [3], Fogh-Anderson [5], Popescu [15], Pitanguy [14] and more recently by Shewmake and Kawamoto [16]. Numerous attempts have been made to classify the facial clefts.…”
Section: Discussionmentioning
confidence: 99%
“…Shewmake [16] and Kawamoto [9] have nicely elucidated the principles of management of cleft nose. They have concluded that each nasal cleft is unique and should be completely evaluated to determine the specific degree of anatomic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…However, certain general treatment principles apply as a foundation for each individual treatment plan: 21,22,[24][25][26] • manage functional problems early; Psychological aspects also play a role.…”
Section: Management Principlesmentioning
confidence: 99%